African universities on a global ranking scale: Legitimation of knowledge hierarchies? - Ndofirepi, A. (South African Journal of Higher Education, 2017)
In this theoretical paper, I argue that the interconnection between the excruciating superiority of the West to conflate its own prototype of society with the ideal state of being is manifested through the heirarchisation of knowledge in the name of the university global rankings. My case is that by accepting the centre–periphery disjunction within the knowledge–power dynamic through situating African universities within the global university rankings is only an entrenched fashion of endorsing the legitimation of the heirarchisation of knowledge. Ranking universities on the league table puts western scientific knowledge systems at the epitome against the local and African indigenous knowledges seating at the bottom of the global knowledge ladder. Arguing from a critical theory perspective, I submit that the elite universities domiciled in the world’s wealthiest economies enjoy a disparate influence over the international standards for scholarship and knowledge processes while denigrating African ways and sources of knowing by placing them at the bottom of the knowledge pyramid. While acknowledging the need for excellence and competitiveness on a global scale, I advance and provide strong evidence that knowledge processes in African universities should not be measured against western –dominated processes due to the uniqueness of each. Conversely, I forward the case that each system of knowing is distinct and placing them on an equal pedestal is indefensible and therefore illegitimate. To that end, I make proposals for African universities to find alternatives to global university rankings that measure their own competitiveness.